Bangla Version of the Boston Carpal Tunnel Questionnaire: Translation, Cross-Cultural Adaptation, Validation and Reliability Assessment - Hasan, Md Israt; Emran, Mohammed; Atiquzzaman, Md; Morshed, Taufiq; Ahmed, Syed Mozaffar; Hasan, ASM Mainul; Chowdhury, Ziaur Rahman (KYAMC Journal, 2022)
Background: Self-reported instruments are outstanding predictor of symptom severity and functional status, hence represent a patient’s view and capture the full extent of disability. The Boston Carpal Tunnel Questionnaire (BCTQ) is a patient reported self-assessment tool for the peoples with Carpal Tunnel Syndrome (CTS). Objective: Our intension was to develop a reliable, validated and culturally adapted Bangla version of original BCTQ (B-BCTQ). Materials and Methods: The B-BCTQ was succeeded following a structured process that included translation, verification, compromise assessment, reverse translation, feedback, and final correction. B-BCTQ reliability and validity were conducted in 48 CTS patients. The reliability was evaluated by performing internal consistency and test–retest analyses. Its validity was assessed by comparing the B-BCTQ with the Physical functioning subscale (PF-10) of Short Form health Survey (SF-36) scale. Results: Cronbach’s alpha was 0.89 for symptom severity scale (SSS) and 0.86 for functional status scale (FSS). Also, Intra-class Correlation Coefficients (ICCs) were calculated as 0.86 for SSS and 0.91 for FSS. Pearson correlation (0.80 for SSS and 0.83 for FSS) analysis demonstrated that the B-BCTQ score was significantly correlated with the PF-10 of SF-36. All of the items were statistically significant (P<0.001). Conclusion: The B-BCTQ is successfully adapted. The study findings support the previous English version indicating its validity and reliability. KYAMC Journal Vol. 13, No. 01, April 2022: 24-31